بلاغة الفعل الكلامي في الخطاب السياسي: خطاب الإعلام السياسي المقاوم بين عامي 2006-2011 م. أنموذجا - بصل، محمد إسماعيل; سعيد، فراس خليل (جامعة تشرين, 2016)
لم تعد البلاغة في المفهوم اللغوي الحديث مجرد دراسة جمالية للعبارة والوقوف على ما تمتلكه من مقومات جمالية، بل تعداها إلى الوقوف على ما يمكن أن يحيل إليه هذا العنصر البلاغي في السياق الذي ورد فيه، لذلك نجد علماء اللغة المحدثين يدرسون الخطاب - أيا كان نوعه - انطلاقا من الفعل الكلامي الذي يتكفل بتحويل الأقوال إلى أفعال ذات صبغة اجتماعية، فالكلام ليس تبادلا للمعلومات فحسب، بل هو تحقيق لأفعال في الواقع وفق مجموعة قواعد من شأنها تغيير وضعية المتلقي وتنظيم منظومة معتقداته ووضعه السلوكي، وفي عالم مليء بالعلامات وخطابات مشبعة بالدلالات يحاول أصحابها الظفر بالمتلقي، كان لخطاب الإعلام السياسي دور كبير في تحديد سلوكيات المتلقي بشكل أو بأخر.
The Eloquence in the speech concept has no longer been just an esthetic study of the phrase or the full understanding of its esthetic aspects. Moreover ,it is the full understanding of the eloquentic element in its context ;that is why we find that all the modern linguistics study the discourse -regardless to its type-starting from the speech acts which are responsible for changing the speeches to acts with a social character .Furthermore, the speech is not only an information exchange ,but also acts representing in the real life according to a set of rules that can change the situation of the receiver and organize his believes and behaviour. Finally ,in a world full of signs and semantic speeches which their senders try to acquire the receiver, we notice that the political media discourse has a basic role in specifying the receiver's behaviours in a way or another.
Keywords: وسائل الإعلام -- الخطب السياسية -- تحليل الخطاب -- البلاغة العربية